The role of organisation culture in achieving competitive advantage at telkom Kenya limited - Anyembe, Macktilder Makhoba; Bowen, Jeptepkeny; Sang, Hellen (My University, 2022)
This study aimed to explore organisational culture's role in achieving competitive advantage in Telkom Kenya. The fact that Telkom was the first Telecom Company in Kenya and yet its performance is low instead of being the market leader justified this study. The study was anchored on Michael Porter's theory of competitive advantage, resource-based review theory and stakeholder theory. Case Study Research Design was used. Data collection was done using questionnaires. A pilot test was used to test the survey's reliability. The questionnaires were administered to twenty employees of Telkom Kenya in Nakuru who were not part of the final study. The Cronbach coefficient alpha test was used to determine the questionnaire's reliability. The analysis of data was by inferential and descriptive statistics. The study established that leadership style and control system statistically impact Telkom Kenya's competitive advantage with beta values of 0.243 and 0.230, respectively. The study concluded that the efforts put so far by Telkom Kenya to achieve competitiveness are not sufficient since its competitors still have the edge over it in the market. The study recommended that Telkom Kenya consider changing its leadership style to one that is participatory and implements control systems to ensure continuous monitoring and evaluation of its performance.
Keywords: Organisational culture; competitive advantage; telkom Kenya